Guiné-Bissau/África: diretrizes tecnológicas para uma política habitacional sustentável - Seabra, Quintino Augusto Có de (Universidade Federal de São Carlos, 2013)
This research purposed to identify, classify and analyze the technologies and raw materials used in low-income housing, as aid for the definition and implementation of a housing policy that can be incorporated sustainability principles and guidelines. The object of empirical study it's Guinea Bissau, in particular Bissau the main town of the country that is located in West Africa and it has one of the world's lowest Human Development Index HDI . Among the various dimensions that make up sustainability, it was decided to prioritize research in environmental and cultural dimensions, considering the country's social and environmental peculiarities. At the start, warned understanding deeply variables and their parameters that characterize a condition of greater sustainability, always focusing on the specific location. At the same mode, it was made a qualitatively and quantitative survey of technologies and materials usually employed in construction for housing, following, it was held a mutual comparison between those variables, parameters and the information collected about the technologies adopted. Together with the scientific aspect, this research aims also to contribute with technological guidelines for structuring a sustainable housing policy of social interest to Guinea Bissau.
Keywords: Habitação social; Sustentabilidade habitacional; Política habitacional; Habitação popular; Guiné-Bissau; Diretrizes tecnológicas; Low income housing; House sustainable; Housing policy; Popular housing in Guinea Bissau; Technological guidelines; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO